THE IMPACT OF FINANCIAL RATIOS ON PRICE TO BOOK VALUE (PBV) IN AUTOMOTIVE AND COMPONENT SUB SECTOR LISTED IN IDX WITHIN 2007-2016 PERIODS - Lebo, Theresia C.; Saerang, David P.E; Tasik, Hizkia H.D (Universitas Sam Ratulangi, 2017)
Abstract: An automotive industry has an important role in boosting Indonesia's economic growth. Every company has an expectation to sustainably operate, but there are financial risks that may interupt the operation. Therefore the automotive and component industries need an assessment of financial performance as a description of the financial condition. If the financial performance is good then the firm value will be good. One indicator that affects the firm value is price to book value (PBV). PBV can be used to indicate about the stock value. The purpose of this research is to determine the impact of financial ratios on the price to book value (PBV). For this purpose the study, use the data of 12 companies listed in IDX from 2007-2016 periods and a panel data regression with random effect model. Based on results, there are a positive relationships among ROA, current ratio and debt to asset ratio, and the price to book value. In addition, the effect of ROA on price to book value is significant. While the current asset and debts to asset ratio have no significant effect on price to book value.Keywords: roa, current ratio, debt to asset ratio, price to book value, panel data regression